Implementation of the Advanced Encryption Standard 128 Algorithm in the Web-Based Management Information System - Setia Handayani Sinaga; Quido Conferti Kainde; Gladly Caren Rorimpandey (Newinera Publisher, 2026)
The manual management of student dormitory administration at Manado State University presents several challenges, particularly related to record accuracy, service effectiveness, and information protection. This research focuses on the development of a web-based dormitory management information system using the Advanced Encryption Standard (AES) 128-bit algorithm as a data security mechanism, particularly for payment documents. The research method used is a prototype model, which includes communication, rapid planning, modeling, prototype development, and testing. The system is implemented using PHP and MySQL, with the integration of AES-128 encryption in the payment receipt upload feature to ensure data confidentiality. The results of black-box testing show that all system functions run according to user requirements. The implementation of AES-128 has been proven to maintain the security of sensitive data and increase user trust in the system. Key features provided include user registration, room reservations, payments, facility reporting, and notifications, while administrators are given full access rights to manage resident and room data, as well as encrypt and decrypt important information. Overall, this research produces a system that not only improves the efficiency and effectiveness of dormitory management but also strengthens data security aspects. The developed system has the potential for further enhancement through mobile application integration and the implementation of an automated payment system to be more responsive to user needs. Cryptography is a field of science that utilizes mathematical techniques to ensure data and information security, including authentication, integrity, and validity